Trends in postcoronary artery bypass graft sternal wound dehiscence in a provincial population. Issue 3 (August 2014) - Doherty, Christopher; Nickerson, Duncan; Southern, Danielle A; Kieser, Teresa; Appoo, Jehangir; Dawes, Jeffery; De Souza, Michael A; Harrop, Alan R; Rabi, Doreen
Background: It appears that the medical profile of patients undergoing coronary artery bypass graft (CABG) surgery has changed. The impact of this demographic shift on CABG outcomes, such as sternal wound dehiscence, is unclear. Objectives: To quantify the incidence and trends of sternal wound dehiscence, quantify the demographic shift of those undergoing CABG and identify patient factors predictive of disease. Methods: A prospective analysis was performed on a historical cohort of consecutive patients who underwent CABG (without valve replacement) in Alberta between April 1, 2002 and November 30, 2009. The incidence and trends of sternal wound dehiscence were determined. In addition, the trend of the mean Charlson index score and European System for Cardiac Operative Risk Evaluation (EuroSCORE) (capturing patient comorbidities) was analyzed. Univariable analysis and multivariable models were performed to determine factors predictive of wound dehiscence. Results: A total of 5815 patients underwent CABG during the study period. The incidence proportion of sternal wound dehiscence in Alberta was 1.86% and the incidence rate was 1.98 cases per 100 person-years. Although both the EuroSCORE and Charlson scores significantly increased over the study period, the incidence of sternal wound dehiscence did not change significantly. Factors predictive of sternal wound dehiscence were diabetes (OR 2.97 [95% CI 1.73 to 5.10]), obesity (OR 1.55 [95% CI 1.05 to 2.27]) and female sex (OR 1.90 [95% CI 1.26 to 2.87]). Conclusions: The incidence proportion of sternal wound dehiscence in Alberta was comparable with the incidence previously published in the literature. While patients undergoing CABG had worsening medical profiles, the incidence of sternal wound dehiscence did not appear to be increasing significantly.